Pengaruh Metode Pembelajaran Guided Note Taking dan Reading Guided Pada Materi Laju Reaksi Terhadap Pemahaman Konsep Peserta Didik Kelas XI MIA - Sri Sulystianingsih N.D Tiring (Jurnal Ilmiah Wahana Pendidikan, 2021)
Research purposes:1) Knowing there or whether the effect of the methods guided note taking SMA Negeri Magepanda to understanding the conceot of. 2) Knowing there or whether the effect of the methods reading guided SMA Negeri Magepanda to understanding the conceot of. 3) Knowing whether the method of guided note taking is more influential to the understanding of the concept of p participants students of class XI SMA Negeri Magepanda on material rate of reaction in compare with the method of reading guided. Research is a research experiment quasi ( quasi-experimental designs ) design research nonequvalent control group design . The results of the study addressed that : 1) There influence application of methods guided note talking to the understanding of the concept of participant students class XI SMA Negeri Magepanda on material rate of reaction. 2) There influence application of methods reading guided to the understanding of the concept of participant students class XI SMA Negeri Magepanda on material rate of reaction. 3) The guided note talking learning method is more influential on the understanding of the concept of students in class XI SMA Negeri Magepanda on the reaction rate material compared to the reading guided method.